(3OjhGf GdTTJQjs - (3CHhGdMSf Ydj Hf YHO Gddg GdTTJQj GdfejQj GdaGQSj,J (B668 (3g` s
(3ChdgG (B:s
(3gPG GdehTM(B: (3bUOj CfXQ Edi hGfa gPG Gdhge Yfj s
(3BNQgG (B:s
(3hef dG jQi ZjQj acja EaJbGQg hbO Mb ddJSdje hGdfXe hGdfKQ s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B120s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B510 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B131 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdYKeGfjI HMjO CHGO (B(71 893 (3T C (B- (3O(B) s
Keywords: (3GdCOHs